Anterior arthroscopic-assisted fixation of posterior cruciate ligament avulsion fractures. Issue 1 (December 2015) - Huang, Wei; Gong, Xuan; Rahul, Mishra; Priyanka, Shukla; Wang, Changdong; Liang, Xi; Ding, Guoliang; Hu, Ning
Abstract Background Avulsion fractures of the tibial insertion of the posterior cruciate ligament (PCL) have always been regarded as rare injuries. The tibial attachment of the PCL is located in an area, which is difficult to access. Hypothesis To verify the effects of anterior arthroscopic fixation of PCL avulsion fractures. Methods 18 patients with PCL avulsion fracture were included. The inclusion criteria were: (1) the fracture fragment size was greater than 20 mm; (2) surgery in the acute phase of fractures (<3 weeks). The intervention was anterior arthroscopic fixation of fractures. Outcome variables included posterior laxity assessment with KT2000 arthrometer, posterior sag sign, the quadriceps activation test, the reverse Lachman, posterior stress X-rays, range of motion, and the IKDC form assessment. Results Complete osseous union showed in all cases during the follow-up (24–49 months). The posterior laxity assessment demonstrated slight posterior tibia translation (<5 mm) on the femur in 1 patient at 89 N and in 2 at maximal testing. All were stable on the posterior sag sign, the quadriceps activation test, the reverse Lachman and posterior stress X-rays. Two had loss of flexion of about 10° (grade B). Others showed a full range of knee motion. According to the IKDC form assessment, 16 patients were classified as grade A and 2 were classified as grade B. 16 of 18 patients were absolutely pain free, and there was general satisfaction on pain questionnaire. All the patients returned to their pre-injury knee function. No revision surgery was performed. Conclusions The anterior arthroscopic-assisted fixation guided with a tibial PCL guide is a simple and feasible alternative for treating PCL avulsion fractures when the fragment size is larger than 20 mm. Level of evidence Case–control study, Level III.